Clinical Application of Epilepsy Genetics in Africa: Is Now the Time? - Esterhuizen, Alina I.; Carvill, Gemma L.; Ramesar, Rajkumar S.; Kariuki, Symon M.; Newton, Charles R.; Poduri, Annapurna; Wilmshurst, Jo M. (Frontiers in Neurology, 2018)
Over 80% of people with epilepsy live in low-to-middle-income countries where epilepsy is often undiagnosed and untreated due to limited resources and poor infrastructure. In Africa, the burden of epilepsy is exacerbated by increased risk factors such as central nervous system infections, perinatal insults and traumatic brain injury. Despite the high incidence of these aetiologies, the cause of epilepsy in over 60% of African children is unknown, suggesting a possible genetic origin. Large-scale genetic and genomic research in Europe and North America has revealed new genes and variants underlying disease in a range of epilepsy phenotypes. The relevance of this knowledge to patient care is especially evident among infants with early onset epilepsies, where early genetic testing can confirm the diagnosis and direct treatment, potentially improving prognosis and quality of life. In Africa however, genetic epilepsies, are among the most under-investigated neurological disorders and little knowledge currently exists on the genetics of epilepsy among African patients. The increased diversity on the continent may yield unique, important epilepsy-associated genotypes, currently absent from the North American or European diagnostic testing protocols. In this review, we propose that there is strong justification for developing the capacity to offer genetic testing for children with epilepsy in Africa, informed mostly by the existing counselling and interventional needs. Initial simple protocols involving well-recognised epilepsy genes will not only help patients but will give rise to further clinically relevant research, thus increasing knowledge and capacity.